Gender and Inclusion Toolbox: Participatory Research in Climate Change and Agriculture - Jost, Christine; Ferdous, N.; Spicer, TD (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
This manual is a resource and toolbox for NGO practitioners and programme designers interested in diagnostic and action research for gender sensitive and socially inclusive climate change programmes in the rural development context. It is meant to be an easy to use manual, increasing the research capacity, skills and knowledge of its users. Integrating gender and social differentiation frameworks should ideally begin from the start of the programme cycle and be coordinated throughout research, design, implementation, and monitoring and evaluation phases. The data gathered using this toolbox supports this programme work.